Ethical Code of Islamic Psychotherapy in Indonesia - Ahmad Saifuddin (Buletin Psikologi, 2020)
Islamic psychotherapy has been an interesting discussion over the past few years. This is indicated by the number of studies on Islamic psychotherapy, both literature studies and experiments. As a method of psychotherapy, Islamic psychotherapy cannot be separated from ethics code. However, Islamic psychotherapy is based on two principles, namely the science of psychology and Islamic religion. It leads to debate about the form of ethical code of Islamic psychotherapy. This study aimed to provide suggestions for the formulation of a code of ethics in Islamic psychotherapy using literature study. The result is a clear formulation of ethical code of Islamic psychotherapy. The formulation is based on psychology ethics which is then interpreted according to the context of Islamic psychotherapy. It is intended that the perception and implementation of Islamic psychotherapy can be standardized and not leading to ethical violations